Lidocaine Does Not Depress Reflex Dilation of the Pupil. Issue 5 (September 1997) - Larson, Merlin D.; Kurz, Andrea; Sessler, Daniel I.; Dechert, Martha; Tayefeh, Farzin; Bjorksten, Andrew R.
Abstract : Background and Objectives: Pupillary dilation in response to dermatomal electrical stimulation is one method of determining sensory block level during combined epidural and general anesthesia. Use of this technique may, however, be confounded by systemic absorption of epidurally administered local anesthetics. Accordingly, the effects of intravenous lidocaine on the magnitude and duration of reflex pupillary dilation were evaluated. Methods: Six volunteers were each anesthetized twice with desflurane 3.5-6.0%. During one anesthetic, intravenous lidocaine was administered to a plasma concentration of 5.3 ± 1.5 μg/mL. When the plasma concentrations were stable, a 5-second tetanic electrical stimulus was applied. Pupil size was then recorded for 8 minutes. Results: Lidocaine, at plasma concentrations near 5 μg/mL, did not significantly alter the pupillary response to electrical stimulation. In contrast, stimulus-induced increase in heart rate was obliterated. Painful stimulation did not increase systolic blood pressure in either case. Conclusions: Typical plasma lidocaine concentrations observed during epidural anesthesia are unlikely to prevent the use of pupillary responses to evaluate sensory block level.